Doctors, Drugs, and Danger - MARK SULZER; LAUREN COLLEY; MICHAEL HELLMANN; TOM LYNCH (University of Oklahoma Libraries, 2022)
Scholarship on young adult (YA) literature has long attended to the interrelationship of power, ideology, and narrative. Drawing on this scholarship, we examined a nonfiction text about the opiate epidemic. Using critical comparative content analysis (CCCA), our study examined differences in Dreamland (the original version) and Dreamland (the young adult adaptation) to better understand the changing nature of textual representation when youth become the imagined audience. We found that in the youth adaptation of Dreamland, the implied youth reader is (a) provided less information about the opiate epidemic, which is also delivered in a simpler structure; (b) kept at a greater rhetorical distance from people who might be deemed unsavory, and (c) given a more optimistic view of the opiate epidemic in terms of progress achieved rather than action needed. The youth adaptation of Dreamland, therefore, positions youth as needing simplicity, protection, and a sense of optimism. Our analysis demonstrates how the implied youth reader is a textual byproduct of discourses of adolescence/ts. As youth adaptations continue their prominence in the YA marketplace, scholars and teachers should critically engage how youth are positioned as readers and thinkers by the YA publishing industry. Next steps involve additional studies that focus on the implied (youth) reader through CCCA and studies that involve middle and secondary education students, the real readers of these texts. This study is supplemented by an interview with Sam Quinones, the author of the original version of Dreamland.